1998
DOI: 10.1007/s004320050173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cancer risk from conditional cancerogens in produce of livestock fed on species of spurge ( Euphorbiaceae )

Abstract: Special procedures were developed to investigate poisonous milk of lactating goats fed experimentally on aerial parts of the herb Euphorbia peplus L. In extracts of the milk, weakly irritant in the mouse-ear assay, three diterpene ester toxins were detected by techniques of high-performance liquid chromatography. They are of the ingenane structural type: Euphorbia factor Pel (ingenol 20-acetate 3-angelate), Euphorbia factor Pe2 (20-deoxyingenol 3-angelate) and Euphorbia factor Pe4 (20-deoxyingenol-6alpha,7alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…An early nutritional study showed higher consumption of sheep’s and goat’s milk in northern Iran than in lower risk areas 18 . Another study showed that milk of small ruminants fed by a family of Euphorbiaceae flower plants contained diterpene esters, a group of compounds which showed promoting activity in experimental systems 19 . This genus is one of the most species-rich flowering plants, and several of its species occur in the study area 20 .…”
Section: Discussionmentioning
confidence: 99%
“…An early nutritional study showed higher consumption of sheep’s and goat’s milk in northern Iran than in lower risk areas 18 . Another study showed that milk of small ruminants fed by a family of Euphorbiaceae flower plants contained diterpene esters, a group of compounds which showed promoting activity in experimental systems 19 . This genus is one of the most species-rich flowering plants, and several of its species occur in the study area 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Eight compounds in the methanol extracts were identified as major contributors to the differences between CHDG and VPDG: apigenin-7- O -β- d -methylglucuronate (a), hydroxygenkwanin (b), genkwanines O (c), orthobenzoate 2 (d), tiliroside (e), quercetin (f), caffeic acid (g), and naringenin (h). Considering their toxicity [ 48 , 49 , 50 , 51 ], the reduction in the amount of daphnane-type diterpene ester compounds in VPDG might explain the mechanism through which stir-baking with vinegar reduces the toxicity of CHDG. In addition to the aforementioned compounds, other compounds not listed here contributed to the differences between CHDG and VPDG.…”
Section: Discussionmentioning
confidence: 99%